Strategi Komite Olahraga Nasional Indonesia dalam Meningkatkan Prestasi Atlet di Provinsi Kalimantan Tengah - Mambang Mambang; Fatmah Fatmah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
The purpose of this study is to explain and describe the Strategy of the Indonesian National Sports Committee in improving the achievements of athletes in Central Kalimantan province. The type of research used in this study is descriptive with qualitative research methods. Sources of data in this study are primary data, namely the Deputy General Chair of KONI, Deputy Secretary of KONI, Division of Organization and Management, KONI staff, Athletes and Coaches. While secondary data comes from official documents related to this research such as sports medal data acquisition, and data collection techniques using interviews, observation, and documentation. The focus of his research is to get a clear picture of the Strategy of the Indonesian National Sports Committee in improving Athlete Achievements in Central Kalimantan Province. The results of this study are that the KONI Strategy in improving the achievements of athletes in Central Kalimantan Province is already good, because of the five Performance indicators there are three indicators that have gone well, Responsiveness, Responsibility, Accountability while the two indicators have not gone well are Productivity and Quality of Service